TERRITORIAL IDENTITY AND VALUES IN GEOGRAPHICAL EDUCATION - ILOVAN, Oana-Ramona; DULAMĂ, Maria Eliza (Presa Universitară Clujeană, 2016)
In this book, territorial identity and the promotion of diverse territorial values (features, assets) is explored through cultural landscapes in general, urban and rural landscapes in particular, and through territorial education approaches.